1981
DOI: 10.1111/j.1365-2141.1981.tb07261.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐induced Thrombocytopenia: Effect of Heparin Platelet Antibody on Platelets

Abstract: The plasma of two patients with heparin-induced thrombocytopenia has been shown to cause platelet aggregation in the presence of heparin. The platelet aggregating factor was isolated in the IgG reaction of the patients' sera suggesting that it was an antibody. This heparin anti-platelet antibody (HAP-Ab) induced platelet aggregation and release but did not cause platelet lysis, although it fixed complement. Platelet aggregation was inhibited by EDTA and by inactivation of complement. There was a significant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
3

Year Published

1985
1985
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(65 citation statements)
references
References 24 publications
0
61
0
3
Order By: Relevance
“…The HIT antibody screening was carried out by two laboratory tests: the assessment of EIA and by a functional assay the HIPAG test (modified by us) which comprises the assessment of PAT described by Chong in 1981 and 1993 [24,25]. The results of EIA were expressed quantitatively in graded OD ranges, taking into account that the strength of a positive EIA test result correlates strongly with the presence of plateletactivating antibodies and that approximately 5-15% of HIT-positive samples yield a weak positive result, that is OD of 0.900-1.100 in the EIA [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HIT antibody screening was carried out by two laboratory tests: the assessment of EIA and by a functional assay the HIPAG test (modified by us) which comprises the assessment of PAT described by Chong in 1981 and 1993 [24,25]. The results of EIA were expressed quantitatively in graded OD ranges, taking into account that the strength of a positive EIA test result correlates strongly with the presence of plateletactivating antibodies and that approximately 5-15% of HIT-positive samples yield a weak positive result, that is OD of 0.900-1.100 in the EIA [28].…”
Section: Resultsmentioning
confidence: 99%
“…The detection of HIT antibodies was carried out with EIA followed by the detection of their reactivity using the HIPAG test with the application of a two-point definition for a positive assay according to Chong [24,25], and by adding a third point, namely 2.5 U/mL of heparin (HIPAG) to increase the sensitivity of the test. This concentration possibly correlates with one of the lower concentrations of heparin used during CPB [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIT antibodies cause platelets to release ADP [7], and ADP enhances FcgIIa receptor-dependent platelet activation by IgG antibodies such as certain platelet-activating monoclonal antibodies [8]. Polga´r et al [9] found that pretreatment of platelets with the ADP receptor antagonist AR-C66096 blocked FcgIIa receptor-dependent platelet activation by HIT antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…A common feature of these reports was evidence of platelet activation induced by patient serum, plasma, or purified immunoglobulin. [11][12][13][14][15][16][17] HIT: an immune disorder or a consumptive coagulopathy?Doubts persisted regarding the immune basis of HIT. After all, Rhodes and colleagues had also noted that when their patients were deliberately rechallenged with heparin several months after their episode of HIT, thrombocytopenia failed to recur.…”
mentioning
confidence: 99%